Public Librarian's Readiness in Providing Health Related Information - Yun-Ke, Chang; Adiputra, Ketut Dharma; Yang, Lim De (Qualitative and Quantitative Methods in Libraries; Vol 2 No 1 (2013): March 2013 Issue, 2017)
Librarians today are not only expected to take care of books but in fact govern all types of access pertaining to information. The public also regarded libraries as the preferred choice to satisfy their information needs on health-related issues. The reported study attempts to gauge the level of readiness and identify factors that are relevant to perceived readiness that public librarians possess and investigate relationships between respondents‟ characteristics to determine their levels of readiness and intention in providing health information to the public. Our data suggest that self-efficacy and attitude factors contribute the most to determine public librarians‟ readiness to provide health information.